Optimizing Medical Equipment Inventory Management through Web-Based System Implementation for Real-Time Monitoring and Alerts - Mega Wahyu Rhamadani; Abdullah Ardi; Adina Apriyani (J-INTECH ( Journal of Information and Technology), 2026)
Manual inventory processes at PT Borneo Sejahtera Medika resulted in an 18.2% stock discrepancy rate, frequent expired items, and delayed procurement decisions. This study develops and empirically evaluates a web-based inventory management system integrating real-time monitoring, automated expiration alerts, and demand forecasting. A six-month before–after analysis was conducted to measure system impact using discrepancy rate, operational performance indicators, and forecasting accuracy metrics. The results show that the discrepancy rate decreased from 18.2% to 13.6%, representing a relative improvement of 25.27%. Operational performance improved significantly, with stock checking time reduced by 52%, expired items reduced by 57%, and emergency procurement reduced by 31%. The forecasting module achieved a Mean Absolute Percentage Error (MAPE) of 5.00%, indicating acceptable short-term prediction accuracy. These findings demonstrate that the implemented system provides measurable improvements in data accuracy, operational efficiency, and inventory control within a healthcare distribution context.